Supply of pigeonpea genetic resources in local markets of Eastern Kenya - Nagarajan, Latha; Audi, Patrick; Jones, Richard (International Food Policy Research Institute, 2008)
Smallholder producers in marginal and semiarid areas of eastern Kenya have not benefited greatly from research investments made in improvement of crops grown in such environments (sorghum, millet, and legumes, including pigeonpea) either by the international community or the national agricultural research system because of poorly developed seed systems. However, informal and local market purchases are the major sources of seed for non-maize cereals and legumes. In the absence of any formalized seed system for dryland crops, more and more farmers rely on local markets to supply seed during normal and disaster periods. We determined the factors affecting the quantities of pigeonpea traded by vendors during the 2006 short-rains season using simple OLS estimation. We found that the participation of traders and farmers was higher and traded larger quantities of pigeonpea in weekly markets located in areas where seed-based intervention programs in place than in non-intervention areas. Also agro-ecologically, markets located in slightly wetter regions offered more varieties and handled higher sales compared with marketsheds in dry regions. Among the traders, the grain traders dominated through their sheer volume of sales, higher investment, and storage capacity in these markets though the distinction between seeds and grains was poor. Of the vendor characteristics, young, educated vendors traded higher quantities of pigeonpea during the planting season. The amount of time spent selling by different vendors in the village fairs also had a significant influence on the pigeonpea quantity traded. Certain market infrastructure variables such as distance to the local markets and the access to information sources (mobile phones) also significantly influenced the amount of pigeonpea sold among vendors in these markets. The existing pigeonpea value chain in local markets could be improved further, provided proper synergies exist between different actors in the system. This would enhance local crop diversity levels as well as improve access to quality plant materials for farming communities in the marginal environments of eastern Kenya.